Vagueness Markers in Italian: Age variation and pragmatic change - Chiara Ghezzi (FrancoAngeli, 2022)
Moving from a broad socio-pragmatic perspective, this study analyses how speakers of different ages use a class of items and constructions that codify intentional vagueness in Italian. Items as un po' 'a bit', tipo 'kind', diciamo 'let us say', così 'so', e cose del genere 'and things like that', or cosa 'thing' constitute a class of linguistically heterogeneous means that often function in conversation as vagueness markers, i.e. elements by which speakers signal that their knowledge or communication are somehow only tentative, approximate and vague. Their use does not depend on language systemic factors, but is the result of a, more or less conscious, choice of speakers to enhance conversation for different reasons, which include facilitating the flow of conversation, signifying a vague categorization, and, eventually, being polite. Operating at the pragmatic level, vagueness markers represent elements that are readily available to speakers' choices and contribute to characterize individual and generational discourse styles. Through a corpus-based analysis of listeners' phone-ins to a Milan radio station, this study investigates how vagueness markers are used by speakers of different ages in 1976 and in 2010, and how Italian discourse styles have evolved in the last forty years.
Keywords: 300; Italian; vagueness markers; radio phone-ins; pragmatic change; age variation; generational style